Comorbid Physical and Psychiatric Disorders among Elderly Patients: A Study at an Outpatient Clinic in Saudi Arabia - Amr, Mostafa; Amin, Tarek Tawfik; Al Saeed, Usama (اتحاد الاطباء النفسانيين العرب, 2013)
الخلفية: يرتبط زيادة طول العمر وشيخوخة السكان بارتفاع معدل انتشار الخرف والاكتئاب والاضطرابات النفسية الأخرى. ومع ذلك، فإن الأبحاث النفسية بين المسنين في منطقة الخليج تعتبر نادرة نسبياً. الأهداف: تهدف هذه الدراسة المقطعية لاستكشاف الخصائص الديموغرافية والنفسية في 412 مريضاً أعمارهم 60 عاماً أو أكثر من المترددين على العيادات الخارجية في مستشفى رعاية نهائية في المملكة العربية السعودية. الطريقة: أجريت مقابلات مع جميع المرضى وأو مقدمي الرعاية لجمع البيانات عن البيانات الديموغرافية وعوامل الخطر المحتملة وتبعتها إدارة المقابلة السريرية المنظمة لتشخيص الأمراض النفسية التي استندت على الدليل الإحصائي الأمريكي الرابع المعد لتشخيص الأمراض النفسية. النتائج: وجد أن ثلاثة وثلاثون في المئة من العينة يعاني من اضطراب نفسي واحد على الأقل وكانت الاضطرابات الأكثر شيوعاً التي تم تحديدها اضطرابات القلق (31.3%)، والخرف (29.6%) والاكتئاب (26.3%) الخلاصة: تعد الاضطرابات النفسية والقلق بشكل خاص، شائعة بين كبار السن في مرافق الرعاية النهائية وينبغي أن يتحلى الأطباء باليقظة بشكل خاص لاضطرابات القلق، بالإضافة إلى غيرها من الاضطرابات النفسية الشائعة لدى كبار السن مثل الاكتئاب والخرف. Increasing longevity and population aging are being accompanied by a higher prevalence of dementia, depression and other psychiatric disorders. However, psychiatric research among the elderly population in the Gulf region is relatively scant. Aims: This cross sectional study aimed to explore the demographic characteristics, physical comorbidities and the psychiatric profile of 412 patients, aged 60 years and over, attending the outpatient clinics at a tertiary care hospital in Saudi Arabia. Method: Older subjects and/or their caregivers were interviewed to collect demographic data followed by administration of the Structured Clinical Interview for psychiatric diagnoses, which is based on the DSM-IV. Physical comorbidities and their characteristics were recorded onto a data compilation form after thorough review of the patients' available health records. Results: Of the included sample, 63.8% had at least one medical comorbid condition; hypertension, diabetes mellitus and ischemic heart disease were the leading medical comorbid disorders found. Also, 31.6% were found to have at least one neurological comorbid condition; seizures, neuropathic pains and Parkinsonism were the most frequently reported. Thirty-three percent of the sample had at least one psychiatric disorder. \ The commonest identified disorders were anxiety disorders (31.3%), dementia (29.6%) and depressive disorders (26.3%). Conclusion: Both physical and psychiatric disorders are frequently encountered and interrelated among older patients attending tertiary care facilities. Of particular concern was anxiety which was the most prevalent type of psychiatric disorder. Clinicians should be particularly vigilant about anxiety disorders in addition to other common psychiatric disorders in the elderly such as depression and dementia
Keywords: الاضطربات البدنية -- الاضطرابات النفسية -- المسنون -- السعودية